Prediction of Rural Energy Consumption Based on the Gray Theory in Hebei Province - Cui He-rui; Zhang Peng-yu (Institute of Advanced Engineering and Science, 2014)
Rural energy is the cornerstone of the development of economy, as a major agricultural province, the scientific prediction on rural energy consumption is particularly important in Hebei Province. In this paper, the GM(1,1) model of the grey theory was used to predict the rural energy consumption as well as the proportion of total energy consumption ratio of Hebei Province, in 2015 the rural energy consumption would reach 833.18 million tons of standard coal, the total energy consumption ratio would reach 28.39%, and the relative error and posterior test are all qualified. Finally, It can provide a scientific basis for the development of energy strategy planning of Hebei Province, and put forward policy recommendations. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4516